Navy enterprises : evaluating their role in planning, programming, budgeting, and execution (PPBE) - Riposo, Jessie; Blickstein, Irv, 1939-; Friel, John A.; Fell, Kindle; Rand eBooks (Santa Monica, CA : RAND, 2009)
The Navy Enterprise has evolved over the past decade to achieve various objectives from improving efficiencies through lean, six-sigma efforts to producing the workforce of the future. This evaluation of the participation of organizations within the Navy Enterprise in the Planning, Programming, Budgeting and Execution (PPBE) system (1) identifies and describes the current participation of Navy Enterprise organizations in PPBE and (2) identifies and assesses potential alternatives for Navy Enterprise participation. RAND analysts evaluated available documentation and conducted extensive interviews with nearly twenty senior leaders throughout the Navy. The biggest benefit of the Navy Enterprise construct from a PPBE perspective has been the increased communication between resource sponsors, providers, and warfighters, which has helped the Navy to better assess the cost and risk trade-offs of resource-allocation decisions. However, the additional workload borne by the enterprises and additional complexity brought into the PPBE process could be greater than the benefit.
Introduction -- The Navy Enterprise: Governance, Organization, and Other Elements -- A Description of the Planning, Programming, Budgeting and Execution Process and the Role of Enterprises -- Alternative Constructs -- Summary of Findings.
"RAND National Defense Research Institute."
"This research was ... conducted within the Acquisition and Technology Policy Center of the RAND National Defense Research Institute"--Preface.
Includes bibliographical references (p. 43-44).
Also available on the internet via WWW in PDF format.
Keywords: United States. -- Department of the Navy -- Appropriations and expenditures -- Evaluation; United States. -- Department of the Navy -- Evaluation; United States. -- Department of the Navy -- Management -- Evaluation; Logistics, Naval; Program budgeting; Electronic books